Qualitative and quantitative ultrasound attributes of maternal-foetal structures in pregnant ewes - Silva, P. D. A. da [UNESP]; Uscategui, R. A. R. [UNESP]; Santos, V. J. C. [UNESP]; Taira, A. R. [UNESP]; Mariano, R. S. G. [UNESP]; Rodrigues, M. G. K. [UNESP]; Simoes, A. P. R. [UNESP]; Maronezi, M. C. [UNESP]; Avante, M. L. [UNESP]; Vicente, W. R. R. [UNESP]; Feliciano, M. A. R. [UNESP] (Wiley-Blackwell, 2018)
Contents The aim of this study was to examine foetal organs and placental tissue to establish a correlation between the changes in the composition of these structures associated with their maturation and the ultrasonographic characteristics of the images. Twenty-four pregnant ewes were included in the study. Ultrasonography assessments were performed in B-mode, from the ninth gestational week until parturition. The lungs, liver and kidneys of foetuses and placentomes were located in transverse and longitudinal sections to evaluate the echogenicity (hypoechoic, isoechoic, hyperechoic or mixed) and echotexture (homogeneous and heterogeneous) of the tissues of interest. For quantitative evaluation of the ultrasonographic characteristics, it was performed a computerized image analysis using a commercial software (Image ProPlus((R))). Mean numerical pixel values (NPVs), pixel heterogeneity (standard deviation of NPVs) and minimum and maximum pixel values were measured by selecting five circular regions of interest in each assessed tissue. All evaluated tissues presented significant variations in the NPVs, except for the liver. Pulmonary NPVmean, NPVmin and NPVmax decreased gradually through gestational weeks. The renal parameters gradually decreased with the advancement of the gestational weeks until the 17th week and later stabilized. The placentome NPVmean, NPVmin and NPVmax decreased gradually over the course of weeks. The hepatic tissue did not show echogenicity and echotexture variations and presented medium echogenicity and homogeneous echotexture throughout the experimental period. It was concluded that pixels numerical evaluation of maternal-foetal tissues was applicable and allowed the identification of quantitative ultrasonographic characteristics showing changes in echogenicity related to gestational age.
Keywords: foetal development; ovine; pregnancy; ultrasonography